Poly(benzoxazine‐co‐sulfur): An efficient sorbent for mercury removal from aqueous solution - Akay, Sema; Kayan, Berkant; Kalderis, Dimitrios; Arslan, Mustafa; Yagci, Yusuf; Kiskan, Baris (Wiley, 2017)
ABSTRACTA novel sulfur‐rich adsorbent, poly(BA‐ala‐co‐sulfur), was synthesized by reacting allyl functional benzoxazine (BA‐ala) and elemental sulfur. Simultaneous inverse vulcanization and ring‐opening reactions of benzoxazine generated copolymers in several feed ratios. The adsorption behavior of these copolymers was investigated in aqueous solutions containing Hg2+. A three level Box–Behnken design with four factors was applied in order to examine the interactive effect of Hg2+ concentration (ppm), S % in adsorbent, temperature, and pH. The optimum adsorption conditions were determined as: 10.33 ppm Hg2+, 68% S content, 329 K, and pH 6.3. Common isotherm and kinetic models were applied to the experimental data, where the Langmuir isotherm provided the better fit (qmax = 79.36 mg g−1) and the pseudo‐second order fit indicated chemisorption as the process‐controlling step. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2017, 134, 45306.
Keywords: Benzoxazine; box-behnken Design; Mercury Removal; Polybenzoxazine; Response Surface Methodology